PELATIHAN LITERASI MEDIA SOSIAL TERKAIT PENANGGULANGAN HOAKS BAGI SISWA PKBM 26 BINTARO - Muhamad Guruh; Hendri Gunawan; Devi Putri Isnaeni; Nurdinni Tilova; Henni Marlinah (Universitas Pamulang, 2020)
Literacy is the ability to understand, analyze, and deconstruct media imager. The ability to do this is intended so that viewers on this matter especially students as media consumers become aware of the way media is created and accessed. Social media is a positive contributor in the advancement of technology and communication. However, the positive impact of the use of social media is often not paid attention, instead of the negative impact of social media that ultimately happens a lot, where one of them is related to the spread of hoax news Hoaxs are information that is created to cover up the actual information. In other words hoaks can also be interpreted as an effort to distort the facts using information that seems convincing but cannot be verified. Hoaks can also be interpreted as an act of obscuring the real information, by flooding a media with the wrong message in order to cover up the correct message. One of the efforts to increase media literacy is through the implementation of Community Service in the form of discussions and the provision of knowledge held at the PKBM 26 Bintro. With the aim of increasing social media literacy training related to hoax prevention, this activity is carried out by providing contemporary examples and presentations regarding the risks of hoax dispersal.Keywords: Media Literacy, Social Media, Hoaks